Should we ask our Children about Sex, Drugs and Rock & Roll?: Potentially Harmful Effects of Asking Questions About Risky Behaviors - Fitzsimons, Gavan J. (2008)
Research shows that asking questions can fundamentally change behavior. We review literature on this question-behavior effect, which demonstrates that asking questions changes both normal and risky behaviors. We discuss potential explanations for the effect and review recent findings that reveal interesting moderators of the influence of questions on behavior. We then highlight the potential impact of the question-behavior effect in an important public health context: screening adolescents for risky behavior. While medical guidelines emphasize the importance of asking adolescents questions about substance (drug, alcohol) use and sexual behaviors, research on the question-behavior effect suggests that asking adolescents about risky behaviors has the potential to increase the frequency with which they engage in these behaviors. We argue that the act of screening or measuring risky behavior is potentially counterproductive. We emphasize the importance of interventions beyond screening, and suggest ways in which screening can be carried out to minimize its impact. In short, asking questions about behaviors can change behavior, and asking questions about risky behaviors may itself be a risky undertaking.